The complete chloroplast genome of Lilium nepalense (Liliaceae) - Hongzhi Wu; Weiwei Bai; Shuilian He; Yan Zhao; Jingzhi Wu (Mitochondrial DNA. Part B. Resources, 2021)
Lilium nepalense is a useful plant species not only for its showy flowers but also has high medicinal value. In this study, the whole chloroplast genome of L. nepalense was sequenced for the first time. The genome size of L. nepalense, was 152,956bp, with typical tetragonal structure: one large single copy (82,573 bp), one small single copy (17,527 bp), and a pair of inverted repeat regions (IRs, 26,428 bp). The overall GC content was 37.0%. The complete genome contained 131 genes, including 85 protein-coding genes, 38 tRNA genes, and 8 rRNA genes. Phylogenetic analysis showed that L. nepalense was a close relationship between L. leucanthum and L. henryi. Phylogenetic analysis placed L. nepalense under the family Liliaceae.